Determination of some heavy metals in human hair by ultrasonic acid digestion and atomic absorption spectrophotometry - Supaporn Pengping (2018)
The determination of heavy metals in the biological samples of human beings is important for clinical screening procedure and environmental monitoring. In this study, an ultrasonic acid digestion (UAD) and cloud point extraction (CPE) were developed as a sample preparation and preconcentration for determination of Cr, Ni and Pb in human hair samples. Various parameters that influence an ultrasonic acid digestion, such as acid mixture, presonication time, sonication time and temperature of the ultrasonic bath have been investigated. The suitable conditions for UAD were as follow: an acid mixture of 2 ml concentrated HNO3 and 1 ml H2O2, 10 min presonication time, 30 min sonication time and 60°C of temperature of the ultrasonic bath. After digestion with UAD, the sample solutions were preconcentrated by cloud point extraction. Chromium, nickel and lead were complexed with ammonium-pyrrolidine dithiocarbamate (APDC) and Triton X-114 was added as non-ionic surfactant. These complexes were extracted into the surfactant-rich phase, at above its cloud point temperature. The surfactant-rich phase was diluted with methanol prior to its analysis by flame atomic absorption spectrophotometry. The chemical variables that affect the cloud point extraction, such as pH of solution, complexing agent concentration, Triton X-114 concentration and complexing time were optimized. Under optimal conditions, the detection limits for Cr, Ni and Pb were 0.077, 0.161 and 0.249 mg ml -1 , respectively.